2009
DOI: 10.1109/tmi.2009.2017741
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Reader Performance for Lesion-Detection/ Localization Tasks of Anatomical Priors in SPECT Reconstruction

Abstract: With increasing availability of multimodality imaging systems, high-resolution anatomical images can be used to guide the reconstruction of emission tomography studies. By measuring reader performance on a lesion detection task, this study investigates the improvement in image-quality due to use of prior anatomical knowledge, for example organ or lesion boundaries, during SPECT reconstruction. Simulated 67Ga-citrate source and attenuation distributions were created from the mathematical cardiac-torso (MCAT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Several groups have evaluated the performance of anatomical priors for lesion detection (51, 67, 71, 73-76) using either computer observer or human observers for the evaluation. The most common figure of merit is the area under the receiver operating characteristic (ROC) curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have evaluated the performance of anatomical priors for lesion detection (51, 67, 71, 73-76) using either computer observer or human observers for the evaluation. The most common figure of merit is the area under the receiver operating characteristic (ROC) curve.…”
Section: Discussionmentioning
confidence: 99%
“…The most common figure of merit is the area under the receiver operating characteristic (ROC) curve. In general it appears that if the task is to detect lesions with elevated activity, the use of organ boundary does not increase the detection accuracy, while using both organ and lesion boundaries may improve the accuracy, especially when the contrast of activity concentration in lesion and background is high (73, 74, 76). Baete et al (51) compared A-MAP with post-smoothed ML-EM, where the task is detection of hypometabolic regions in brain FDG PET.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we describe a different Hotelling-based model observer that uses features explicitly based on cardiac motion, as described later, not the channelized features used in [9]-[21]. …”
Section: Methodsmentioning
confidence: 99%
“…At present, the most widely used model observer is the channelized Hotelling observer (CHO), a generalized likelihood ratio test, which has been successfully used as a surrogate for human observers in perfusion-defect detection tasks [9]-[21]. It has been shown that the CHO, with or without the inclusion of an internal-noise model, can predict human performance reasonably well in detection tasks for lesions [12], [13] and cardiac perfusion defects [14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation